Specific heteromeric association of four transmembrane peptides derived from platelet glycoprotein Ib-IX complex - Luo, Shi-Zhong (2008)
As the receptor on platelet surface for von Willebrand factor, glycoprotein (GP) Ib-IX complex is critically involved in hemostasis and thrombosis. How the complex is assembled from GP Ibα, GP Ibβ and GP IX subunits, all of which are type I transmembrane proteins, is not entirely clear. Genetic and mutational analyses have identified the transmembrane (TM) domains of these subunits as active participants in complex assembly. In this study, peptides containing the transmembrane domain of each subunit have been produced and their interaction with one another characterized. Only the Ibβ TM sequence, not Ibα and IX counterparts, can form homo-oligomers in SDS electrophoresis and TOXCAT assays. Following up on our earlier observation that a Ibβ-Ibα-Ibβ peptide complex (αβ(2)) linked through native juxtamembrane disulfide bonds could be produced from isolated Ibα and Ibβ TM peptides in detergent micelles, here we show that addition of the IX TM peptide facilitates formation of the native αβ(2) complex, reproducing the same effect by the IX subunit in cells expressing GP Ib-IX complex. Specific fluorescence resonance energy transfer was observed between donor-labeled αβ(2) peptide complex and acceptor-conjugated IX TM peptide in micelles. Finally, the mutation D135K in the IX TM peptide could hamper both the αβ(2) complex formation and the energy transfer, consistent with its reported effect in the full-length complex. Overall, our results have demonstrated directly the native-like heteromeric interaction among the isolated Ibα, Ibβ and IX TM peptides, which provides support for the four-helical bundle model of the TM domains in GP Ib-IX complex and paves the way for further structural analysis. The methods developed in this study may also be applicable to other studies of heteromeric interaction among multiple TM helices.